Does An Antimicrobial Stewardship Program for Carbapenem Use Reduce Costs? An Observation in Tehran, Iran. - Mahboubeh Hajiabdolbaghi; Jalil Makarem; Mohammadreza Salehi; Seyed Ali Dehghan Manshadi; Esmaeil Mohammadnejad; Hossein Mazaherpoor; Arash Seifi (Babol University of Medical Sciences, 2020)
Background: Inappropriate administering of antimicrobials has led to increased antibiotic resistance as well as burden of infectious diseases. Antibiotic stewardship programs (ASPs) help prevent resistance through improved utilization of antimicrobial agents while potentially decrease costs of treatment. Methods: We reviewed 186 infectious disease (ID) consultations from two internal disease wards in a tertiary center where ID specialists were asked to confirm carbapenem use in patients within 48 hours of initiation. The records were reviewed in terms of age, gender, and final decision about carbapenem use. The crude mortality rates during the 5-month period of the study (May to September 2016) as well as hospital spendings were compared with the same time of the year before the implementation of the ASP. Results: Of the 186 consultations conducted by the ID specialists, 28 (15%) consultations led to antibiotic change, 46 (25%) led to discontinuation, while 112 (60%) carbapenems were continued. An estimate of 14,000 € was saved based on the annual hospital costs during the 5-month period of the study. Although antimicrobial resistance patterns could not be evaluated, the crude mortality rate in the two IM wards was calculated to be 2.6% with no significant change compared to previous year (CMR: 2.9%). Conclusion: Based on findings of the present study, ASPs for carbapenems (as widespectrum agents) can lower costs with no increased mortality rates in a tertiary center located in a middle-income country